A flexible carbon nanotube-modified poly(styrene-butadiene)-based dopamine sensor. (9th October 2019) - Cheng, Haiyan; Jin, Wen; Huang, Xinhua; Liu, Xiao; Wang, Feng; Guo, Xiaoyu; Wu, Yiping; Ying, Ye; Wen, Ying; Yang, Haifeng
Abstract: In this work, a multi-walled carbon nanotube-modified flexible poly(styrene-butadiene) fiber membrane material was prepared for the sensitive and selective electrochemical detection of dopamine (DA) in human serum and DA injection. The flexible fiber membrane prepared by electrospinning technology is expected to realize its application in wearable devices. The obtained conductive film-based electrochemical sensor can effectively minimize interference caused by ascorbic acid and uric acid. Under the optimized experimental conditions of differential pulse voltammetry, DA gives a linear response in the range of 1–650 μ M (R 2  = 0.996). The detection limit of DA (signal-to noise ratio = 3) was determined to be 0.062 μ M.